Identification of Accurate Classification Technique for Crime Investigation Using Ensemble Approach - sharma, Sadhna; sharma, Sanjiv (International Journal of Computer Sciences and Engineering, 2019)
Recently, it`s observed that the crime is increasing across the world very rapidly and some technique is required for analysis of the crime data. Analysis of the crime data can be done through data mining (DM). DM techniques are applied to crime data for predicting features that affect the high crime rate. Using the method of data mining on previously collected data for predicting the features responsible for the crime in a locality or area, the Police Department and the Crimes Record Bureau Police Department may take the required measures to reduce the likelihood of the crime. In the current work, a new machine learning ensemble algorithm is opted for predicting feature that affects a high crime rate. It helps the police and citizens to take necessary and required action in decreasing the crimes rate. The ensemble algorithm can predict more accurate and significant features with higher accuracy and efficiency.